Om allokering av straffansvar vid arbete utan tillstånd - Kallio, Heikki (Nordisk Tidsskrift for Kriminalvidenskab, 2024)
Abstract On 23 February 2023, a comprehensive reform of the Aliens Act concerning the employment and business activities of foreign nationals entered into force in Finland. The objective of the reform was to increase the authorities’ ability to prevent the exploitation of foreign labour. One of the most significant changes involved the client´s obligations to ensure the right to work for foreign nationals entering and remaining in employment. These changes were prompted by, among other things, problems identified in the regulatory framework concerning the obligations of the employer and the client and the allocation of criminal liability. The article analyses the allocation of liability for offences related to unauthorised work from the perspective of Finnish legislation. It focuses on how criminal liability has been shared and allocated since the comprehensive reform of Chapter 5 of the Aliens Act was implemented in Finland. The article concludes that after the amendments to the Aliens Act, criminal liability will be allocated in the same way and to the same parties, regardless of whether the Criminal Code’s provision on the unauthorised use of foreign labour or the Aliens Act’s employer’s alienage offence applies in the case under consideration. This can reasonably be seen as reducing the problems of apportioning responsibility for unauthorised employment. As regards the concrete attribution of criminal liability, attention must be focused on the circumstances of the act, the employer organisation and the specific person in that organisation. The starting point for allocating criminal liability must be to determine who is responsible for the offence in the first place within the meaning of the applicable provision. It is then necessary to determine who has the authority to hire and retain employees. Finally, criminal liability must be attributed to the person who actually committed the acts in question.